Atkins diet program rapidly decreases atherogenic index of plasma in trained adapted overweight men - Caminhotto,Rennan de Oliveira (2015)
Background The Atkins diet program is a great example of the application of low carbohydrate diets for obesity, with the intention of weight loss and improvement in cardiovascular risk (CV risk). A good CV risk predictor is the atherogenic index of plasma (AIP) calculated as log (TG/HDL [mmol]), which is strongly affected by serum triglycerides, which in turn is associated with the carbohydrate intake. This study determined the effect of the initial phase of Atkins diet program, consisting in 20 g/day of carbohydrate intake with positive urinary ketones measure, in AIP of 12 adult overweight trained adapted men. The AIP was calculated before and after intervention. Results After 14 days, BMI and triglycerides decreased significantly, while HDL-C increased. No alterations were described in LDL plasmatic concentration. Prior to the diet, 58.3% of subjects presented high CV risk and after 14 days of the diet program only 33.3% of subjects were classified as high CV risk, while more than 66% were low CV risk. The intervention was effective in 11 of 12 participants. However, in one person the dietary intervention increased AIP index. Conclusion The initial phase of Atkins diet program could significantly decrease the AIP in 11 of 12 adult overweight trained adapted men. Dietary individual responses need to be more studied.